VARYING APPLICATION OF MOST-FAVOURED-NATION PRINCIPLE IN INTERNATIONAL INVESTMENT TREATY - Mahardika, Robertus Bima Wahyu; Latifah, Emmy (Yustisia, 2018)
The aim of this study is to provide an academic framing of the philosophical foundation of the Most-favored-nation principle (MFN) in international investment law. The MFN principle is one of the most important principles in international law. In international investment law, MFN principle serves as a mechanism to create conditions in which foreign investors from many countries have equal opportunities to compete fairly in host country.